CO2 Emissions, Health Expenditures and Economic Growth in Iran: Apply Dynamic Simultaneous-Equations Models - Naghmeh Ghorashi; Abbas Alavi Rad (Shahid Sadoughi University of Medical Sciences, 2017)
Introduction: The causal dynamics between environment, health expenditures and economic growth has recently started to be studied in the economics literature for both developing and developed countries. Methods: This study examines the causal relationship between CO2 emissions, health expenditures and economic growth using dynamic simultaneous-equations models for Iran over the period 1972-2012. Results: Our empirical results show that there is bidirectional causality relationship between CO2 emissions and economic growth; there is also unidirectional causality relationship from health expenditures to economic growth. The positive bidirectional causality relationship between CO2 emissions and economic growth will be very important to environmental quality in next years in Iran. Conclusion: It is clear that government would like to increase economic growth over the period of next Five-Year Development Plan. It seems that policymakers must examine the requirements for investment to promote environmental protection and increase the technological transfer to reduce the environmental damage.